The The Use of Storyline Online Website by EFL Learners as The Independent Learning Media to Learn Listening Comprehension - Putri Wulandari; Aldha Williyan; Virga Putra Darma (Tomorrow's Education Journal, 2024)
This study aims to explore the use of the Storyline online website for learning listening comprehension and also find out the benefits and challenges EFL learners perceive when using the Storyline Online website as a self-learning tool to learn listening comprehension skills. The methodology for this study is qualitative, using a descriptive research design. The participants of this study were 3 students from class XI RPL 2 who were selected by criterion-based sampling. For this study, the researcher employed interviews, focus group discussions and documentation methods to gather the necessary information. The researcher used Miles and Huberman's method to analyze the data. The results of this study show that the online storyline website is used to learn to listen for gist, listen for specific information, listen for details and inferential listening. Storyline online has several benefits and challenges. The benefits of storyline include practicing listening comprehension, vocabulary acquisition, pronunciation, inspiring stories and easy to use. While the challenges in learning to use storyline include unfamiliar vocabulary, fast pronunciation and accents.